Safety of Gam-COVID-Vac (Sputnik V) Combined Vector Vaccine in Patients With Immunoinflammatory Rheumatic Diseases: Preliminary Data - A. N. KULIKOV; N. V. MURAVYEVA; B. S. BELOV (Антибиотики и Химиотерапия)
Background. Patients with autoimmune and inflammatory rheumatic diseases (AIRDs) are at high risk of developing COVID-19. Vaccination is an effective method of preventing this disease, which may be unsafe for patients with AIRDs.The aim of the study is to assess the safety of Gam-COVID-Vac in patients with IVRD in real clinical practice.Material and methods. A cross-sectional study was carried out. The main group consisted of patients with AIRDs, the control group consisted of individuals without AIRDs. All participants were interviewed by the research physician using a unified questionnaire, additional information was obtained from medical records.Results. The study included 222 patients with AIRDs (119 with rheumatoid arthritis, 36 with ankylosing spondylitis, 17 with psoriatic arthritis, 17 with Sjögren's disease, 10 with undifferentiated spondyloarthritis, 8 with systemic lupus erythematosus, 4 with metabolic arthritis, 3 with systemic scleroderma, 3 with systemic vasculitis, 2 with polymyalgia rheumatica, 2 with undifferentiated systemic connective tissue disease, 1 with adult Still's disease) and 111 patients without AIRDs. The number of patients with AIRDs who had a combination of local and systemic adverse events (AE) on the introduction of the first component of the vaccine was significantly less than in the control group (22.1 and 44.1%, respectively, P<0.001). Similar differences were also noted after the introduction of the second component (14.0 and 29.7%, respectively, P<0.001). AEs such as pain at the injection site without restriction of movement, weakness, fever, arthralgia/myalgia, headache, and chills were significantly more common in the control group after the introduction of the first component of the vaccine. After complete immunization, AEs were absent in 35.6% of patients with AIRDs and in 21.6% of control group patients (P=0.01). Exacerbations of AIRDs and new autoimmune phenomena were not registered in any cases.Conclusions. According to preliminary data, immunization of patients with AIRDs with the Gam-COVID-Vac combined vector vaccine appears to be quite safe.